Diagnostic performance of C-TIRADS combined with SWE for the diagnosis of thyroid nodules - Gao, Xiao-Qiang; Ma, Yue; Peng, Xiao-Shan; Wang, Ling-Ling; Li, Hai-Xia; Zheng, Xiu-Lan; Liu, Ying (Frontiers in Endocrinology, 2022)
Objective To explore the value of the optimal parameters of shear wave elastography (SWE) to enhance the identification of benign and malignant thyroid nodules by C-TIRADS. Methods The two-dimensional ultrasonography images and SWE images of 515 patients with a total of 586 thyroid nodules were retrospectively analyzed. The nodules were divided into the D ≤10 mm and D >10 mm groups according to size and were graded by C-TIRADS. With the pathological results as the gold standard, the receiver operating characteristic (ROC) curves were drawn, and the area under the curve (AUC) was calculated to compare the diagnostic performances of C-TIRADS, SWE, and the combination of the two on the benign and malignant thyroid nodules. Results The ROC showed that the AUC of the maximum elastic modulus (0.875) was higher than that of the mean elastic modulus (0.798) and elasticity ratio (0.772), with an optimal cutoff point of 51 kPa, which was the optimal parameter to distinguish the malignant from the benign nodules (P < 0.001). In the D ≤10 mm group, the AUC of TIRADS combined with SWE (0.955) was elevated by 0.172 compared with the application of C-TIRADS alone (0.783), and the difference was statistically significant (P < 0.05). In the D >10 mm group, the AUC of TIRADS combined with SWE (0.904) was elevated by 0.076 compared with the application of C-TIRADS alone (0.828), and the difference was statistically significant (P < 0.05). Among all nodules, the application of C-TIRADS alone had a sensitivity of 88.14%, a specificity of 74.56%, and an accuracy of 85.50% in diagnosing benign and malignant thyroid nodules, while the sensitivity, specificity, and accuracy were 93.22%, 90.35%, and 92.66%, respectively, in combination with SWE. Conclusion The diagnostic performance of SWE in combination with TIRADS was better than that of SWE or C-TIRADS alone. Here, SWE enhanced the diagnostic performance of C-TIRADS for the benign and malignant thyroid nodules, most significantly for nodules with D ≤10 mm.